2016
DOI: 10.1007/s11207-016-1039-2
|View full text |Cite
|
Sign up to set email alerts
|

Historical Auroras in the 990s: Evidence of Great Magnetic Storms

Abstract: Recently, a significant carbon-14 enhancement in the year 994 in tree rings has been found, suggesting an extremely large cosmic ray flux event during a short period. The origin of this particular cosmic ray event has not been confirmed, but one possibility is that it is of solar origin.Contemporary historical records of low latitude auroras can be used as supporting evidence for intense solar activity around that time. We investigated the previously reported as well as the new records found in contemporary ob… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

6
3

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 45 publications
(80 reference statements)
1
41
0
Order By: Relevance
“…In order to identify the origin of such cosmic ray events, survey of auroras and sunspots in historical documents have been conducted (e.g. Allen 2012; Usoskin et al 2013;Stephenson 2015;Hayakawa et al 2017a;Tamazawa et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to identify the origin of such cosmic ray events, survey of auroras and sunspots in historical documents have been conducted (e.g. Allen 2012; Usoskin et al 2013;Stephenson 2015;Hayakawa et al 2017a;Tamazawa et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Keimatsu 1970;Vaquero & Vázquez 2009;Hayakawa et al 2015Hayakawa et al , 2017a. Therefore, discussing about historical records on naked-eye sunspots and low-latitude auroras can provide more detailed insights and information on past solar activity, and hence attracted several authors to the original historical documents written in various areas and languages 1 .…”
Section: Introductionmentioning
confidence: 99%
“…If one can identify clear evidence of the occurrence of extremely large sunspots or intense auroras in the historical records, it can provide a strong support for the "superflare" scenario of the 14 C events. Several independent works have been recently published with regards to this scenario Neuhäuser & Hambaryan 2014;Zhou et al2014;Chapman et al 2015;Stephenson 2015;Hayakawa et al 2016a;Hayakawa et al 2016f). …”
Section: Introductionmentioning
confidence: 99%
“…Silverman, 1995Silverman, , 2006Silverman, , 2008Silverman and Cliver, 2001;Nevanlinna, 2004Nevanlinna, , 2006Nevanlinna, , 2008Shiokawa et al, 2005;Vaquero et al, 2008;Cliver and Dietrich, 2013;Viljanen et al, 2014;Lefèvre et al, 2016;Lockwood et al, 2016Lockwood et al, , 2018Vennerstrom et al, 2016;Riley et al, 2018), while recent studies have identified extreme magnetic storms before magnetic observations became available continuously with eyewitness auroral records (e.g. Willis et al, 1996aWillis et al, , 2005Willis et al, , 2007Willis and Stephenson, 2001;Hayakawa et al, 2017aHayakawa et al, , 2017bHayakawa et al, , 2017cHayakawa et al, , 2018Ebihara et al, 2017).…”
mentioning
confidence: 99%